Commodification of the gospel and the socio-economics of neo-Pentecostal/Charismatic Christianity in Ghana - Benyah, Francis (Legon Journal of the Humanities, 2018)
In Africa, religion, generally, has often been used as a medium to assuage difficulties in life. The pragmatic-oriented function of religion, as found in Africa’s economy of faith, makes religion a kind of an economic good/service that can be harnessed to deal with existential needs and aspirations. Operating within this worldview, and with the help of the media, some Ghanaian Pentecostal/Charismatic pastors-prophets have commodified the gospel by employing various means of marketing to advertise, brand, and package religion as a consumer or spiritual product that can be bought to solve life-debilitating issues. This article focuses on some of the contemporary practices of the neo-Pentecostal/Charismatic churches that are symptomatic of the commercialization and the commodification of religion. In so doing, the article attempts to tease out the positive and negative socio-economic implications of these practices. The work demonstrates that though there are some deleterious implications of the commodification of the gospel, the neo-Pentecostal/Charismatic churches, through such practices, have been able to raise substantial amounts of money to fund numerous social intervention projects that are helping transform the lives of people. Data used in this article was gleaned from the radio, television, and relevant literature.
free
Keywords: Pentecostalism; charismatics; commodification; consumer; socio-economic development.